Physical properties of artificial teeth after immersion in liquid disinfectant soaps - De Oliveira Zoccolotti, Jacqueline [UNESP]; Suzuki, Rafaella Barbosa [UNESP]; Rinaldi, Talita Baptista [UNESP]; Pellissari, Claudia Viviane Guimaraes [UNESP]; Sanità, Paula Volpato [UNESP]; Jorge, Janaina Habib [UNESP] (My University, 2019)
Purpose: To evaluate the hardness, roughness and color stability of artificial teeth after immersion in liquid disinfectant soaps. Methods: Artificial teeth (Vipi Dent Plus, ArtiPlus and Biolux) were divided into four groups (n=15), according to the type of immersion solution: distilled water/control group (DW); liquid disinfectant soap Dettol (SD); liquid disinfectant soap Protex (SP); and liquid disinfectant soap Lifebuoy (SL). The immersion cycles occurred every day, for 8 hours at room temperature in each disinfectant solution, following immersion in distilled water for 16 hours at 37°C. All solutions were changed daily. Properties were evaluated after 0, 7, 14, 21 and 28 days of immersion. The data were analyzed with a mixed three-way ANOVA followed by the Bonferroni post-hoc test (a= 0.05). Results: Vipi teeth presented significant reduction (P< 0.05) in hardness and roughness prior to 7 days of immersion in all solutions, including control group. These values, in general, were maintained during the 28 days. Biolux teeth, in general, did not present significant changes in hardness prior to immersion in any of the time intervals. The roughness of these teeth increased after 21 and 28 days of immersion (P< 0.05) in all the solutions. ArtiPlus teeth maintained stable roughness and hardness during the assessment period, regardless of the type of soap used. Color alterations were considered clinically acceptable. The liquid soaps may be an alternative for the disinfection of partial or total removable dentures. (Am J Dent 2019;32:14-20).